Preclinical modeling of cytosine arabinoside response in Mll-Enl translocator mouse leukemias. - Cano, F; Pannel, R; Follows, G; Rabbitts, T (2008)
Mouse models of human cancer are a potential preclinical setting for drug testing and for development of methods for delivery of macromolecular drugs to tumors. We have assessed a mouse model of leukemia caused by Mll-Enl protein fusion as a preclinical situation in which myeloid-lineage leukemia results from de novo occurrence of chromosomal translocations between Mll and Enl genes. Here, we show that the mouse leukemias respond to cytosine arabinoside, a frontline treatment for human leukemia. The observations show that the myeloid cells are susceptible to the drug and the mice undergo a remission that comprises a reduction of the myeloid population of cells and recovery of the lymphoid population. This translocator model should therefore prove useful for future drug assessments against the recurrent mixed-lineage leukemia-associated translocations.